Methods for the Administration of EDAR Pathway Modulators in Mice - Schuepbach-Mallepell, Sonia; Kowalczyk-Quintas, Christine; Dick, Angela; Eslami, Mahya; Vigolo, Michele; Headon, Denis J.; Cheeseman, Michael; Schneider, Holm; Schneider, Pascal (The TNF Superfamily, 2021)
Genetic deficiency of ectodysplasin A (EDA) causes X-linked hypohidrotic ectodermal dysplasia, a congenital condition characterized by the absence or abnormal formation of sweat glands, teeth, and several skin appendages. Stimulation of the EDA receptor (EDAR) with agonists in the form of recombinant EDA or anti-EDAR antibodies can compensate for the absence of Eda in a mouse model of Eda deficiency, provided that agonists are administered in a timely manner during fetal development. Here we provide detailed protocols for the administration of EDAR agonists or antagonists, or other proteins, by the intravenous, intraperitoneal, and intra-amniotic routes as well as protocols to collect blood, to visualize sweat gland function, and to prepare skulls in mice.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Amniotic fluid; Ectodermal dysplasia; EDAR signaling; Protein replacement therapy; Route of administration